Diskursivno-stilišističeskij podhod k izučeniû naučnogo teksta - Baženova, Elena A. (Stylistyka, 2021)
The article reviews the correlation between the discourse theory and the theory of functional stylistics. Based on the similarity of the most important methodological principles of these linguistic directions, the author suggests these directions should be integrated in the discourse and stylistic approach. This approach is applied to scientific texts. The discourse component of this approach allows to identify extral inguistical factors of scientific communication; the stylistic component allows to discover the linguistic devices that represent the standard content of a scientific paper. The author develops the concept of epistemical situation and considers the latter to be discourse metamodel of a scientific texts, which determines its stylistic peculiarity. The structure of epistemical situation is described with regard to the four interconnected aspects of cognitive activity: ontological, methodological, reflective, communicative-pragmatical. The author reveals the content of each aspects and analyses their influence on the sense structure of a scientific text. The author considers the subtext to be a structural element of the text and describes the primary subtexts: the subtext of a new and old knowledge, the subtext of evaluation, the subtext of recipient and the author, etc.